2021
DOI: 10.1002/cmdc.202100149
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Dipeptide: A Privileged Molecular Scaffold to Derive Structural Diversity and Functional Utility

Abstract: Cyclic dipeptides (CDPs) are the simplest form of cyclic peptides with a wide range of applications from therapeutics to biomaterials. CDP is a versatile molecular platform endowed with unique properties such as conformational rigidity, intermolecular interactions, structural diversification through chemical synthesis, bioavailability and biocompatibility. A variety of natural products with the CDP core exhibit anticancer, antifungal, antibacterial, and antiviral activities. The inherent bioactivities have ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 166 publications
(475 reference statements)
2
43
0
Order By: Relevance
“…The scaffold is the main fragment of compound (e.g., ring system) after removal of substituents (R-groups) [71,72]. The privileged molecular scaffold is defined as a core structure, which forms structurally diverse bio-molecules via introducing different functional groups [73,74]. DKPs can play the role of a privileged, multi-functionalized scaffold for the design and development of advanced therapeutic agents, drug delivery systems, biomaterials, or bio-imaging to mitigate numerous disease conditions, also as for the synthesis of complex natural products [74] because of their specific conformational and physico-chemical attributes.…”
Section: Dkp Scaffoldmentioning
confidence: 99%
See 3 more Smart Citations
“…The scaffold is the main fragment of compound (e.g., ring system) after removal of substituents (R-groups) [71,72]. The privileged molecular scaffold is defined as a core structure, which forms structurally diverse bio-molecules via introducing different functional groups [73,74]. DKPs can play the role of a privileged, multi-functionalized scaffold for the design and development of advanced therapeutic agents, drug delivery systems, biomaterials, or bio-imaging to mitigate numerous disease conditions, also as for the synthesis of complex natural products [74] because of their specific conformational and physico-chemical attributes.…”
Section: Dkp Scaffoldmentioning
confidence: 99%
“…The privileged molecular scaffold is defined as a core structure, which forms structurally diverse bio-molecules via introducing different functional groups [73,74]. DKPs can play the role of a privileged, multi-functionalized scaffold for the design and development of advanced therapeutic agents, drug delivery systems, biomaterials, or bio-imaging to mitigate numerous disease conditions, also as for the synthesis of complex natural products [74] because of their specific conformational and physico-chemical attributes. DKPs are heterocyclic compounds consisting of two amino acid residues linked to a central six-membered lactam ring core with (or without) various substituents, providing the control of the substituent's stereochemistry at up to four positions, chiral nature, three-dimensionality, and consequently leading to the promotion of the intermolecular H-bonding interactions with bio-target sites via the corresponding sites of donors and acceptors [17].…”
Section: Dkp Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategies for preparing the new generation of dipeptide hydrogels can be divided into four categories based on the modification site of dipeptide: 1) N-terminal modified dipeptide; 2) C-terminal modified dipeptide; 3) uncapped dipeptide; 4) cyclic dipeptide. This review will focus on the linear dipeptide (1-3) and other recent reviews about cyclic dipeptide can be found in articles by Yu et al (2020) and Balachandra et al (2021).…”
Section: The Structures Of Self-assembly Dipeptide Hydrogelatorsmentioning
confidence: 99%